2017
DOI: 10.2166/wcc.2017.121
|View full text |Cite
|
Sign up to set email alerts
|

Changes in climate zones across Turkey

Abstract: Turkey lies in a critical region that is projected to be one of the most vulnerable to the impacts of climate change in the Mediterranean region. In this study, climatic zones of Turkey were classified with respect to their climatic and meteorological characteristics. The Thornthwaite precipitation efficiency index was used to identify aridity and humidity characteristics. The index values were mapped to determine climate zones and associated climate classes and to evaluate change in time and space. Two distin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 11 publications
0
6
0
1
Order By: Relevance
“…1 a). Research suggests that three major climates occur in Turkey ( Deniz et al, 2011 ; Iyigun et al, 2013 ; Selek et al, 2018 ). These, as is known, are Terrestrial Climate, Black Sea, and Mediterranean Sea Climates (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1 a). Research suggests that three major climates occur in Turkey ( Deniz et al, 2011 ; Iyigun et al, 2013 ; Selek et al, 2018 ). These, as is known, are Terrestrial Climate, Black Sea, and Mediterranean Sea Climates (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 110 cases of scorpion stings was reported in 2017. In the same way, Turkey with the Mediterranean climate zone is pointed up for the incidence of scorpion stings [ 32 ]. In a study in 2008, Ozkan et al [ 16 ] reported 24,261 scorpion sting cases in Turkey in 2005.…”
Section: Discussionmentioning
confidence: 99%
“…Şekil 2. Endüstri 4.0'ın yapısı (Selek, 2017) Genel olarak bakıldığında bilişimin hızla yayılması, teknolojiye erişimin ucuzlaması ve ulaşılabilirliğinin kolaylaşması, bilgisayarların iş ve toplumsal hayatın hemen hemen her noktasına girmesi bilgi toplumunu oluşturmuş ve bu durum da Endüstri 4.0'ı ortaya çıkarmıştır. Endüstri 4.0 bilgiye erişimin geleneksel yapısını da derinden etkilemiştir.…”
Section: Endüstri Devrimiunclassified